Carbohydrate Partitioning and Antioxidant Substances Synthesis Clarify the Differences Between Sugarcane Varieties on Facing Low Phosphorus Availability - Tarumoto, Miriam Büchler; de Campos, Murilo; Momesso, Letusa; do Nascimento, Carlos Antônio Costa; Garcia, Ariani; Coscolin, Renata Bruna dos Santos; Martello, Jorge Martinelli; Crusciol, Carlos Alexandre Costa (Frontiers in Plant Science, 2022)
Phosphorus (P) availability is important for metabolic process, tillering and formation of a vigorous root system in sugarcane, but sugarcane varieties differ in P uptake efficiency. This study evaluated the enzymatic, nutritional, and biometric parameters of two sugarcane varieties under two conditions of P availability by monitoring the initial development of plants grown in nutrient solution. The experiment was performed using randomized complete block design (RCBD) with five replicates and included two varieties, RB966928 (high nutritional requirements) and RB867515 (low nutritional requirements), and two concentrations of P in the nutrient solution: low (2 mg L−1) and suitable (16 mg L−1). Carbohydrate concentrations and partitioning, leaf nutrient concentrations, enzymatic activity, and shoot and root biometric parameters were analyzed. Regardless of sugarcane variety and the part of the plant, reducing sugar were approximately 32.5% higher in RB867515 and 38.5% higher in RB966928 under suitable P compared with low P. Sucrose concentrations were significantly higher in both varieties under suitable P than in low P. According to PCA, the relationship between reducing sugars and sucrose was closer in RB966928 than in RB867515. Under low P, soluble protein content decreased, and the activities of the antioxidant enzymes superoxide dismutase (SOD), catalase (CAT), and ascorbate peroxidase (APX) and the concentrations of hydrogen peroxide (H2O2), and malondialdehyde (MDA). The variety RB966928 under suitable P appears to have a high capacity for proline (120%) upregulation under abiotic stress compared with RB867515 (54%), and thus higher biomass accumulation of this RB966928 variety; however, RB867515 had superior results compared to RB966928 under low P. Suitable P increased leaf concentrations of N, P, Mg, B, and Mg and decreased leaf Zn content. Root and shoot dry matter, root length, plant height, and root and stalk diameter increased by suitable P. Regardless of variety, both nutritional and biometric parameters were directly influenced by P levels, including sugarcane yield. In relation of sugarcane dry matter, RB966928 was less sensitive to low P levels and more responsive to P supply than RB867515 and thus may be more suitable for environments in which P is limiting.